Influence of grain size on burrowing and alongshore distribution of the yellow clam (Amarilladesma mactroides) - Fiori, Sandra Marcela (2015)
The yellow clam Amarilladesma mactroides (Reeve, 1854), is an intertidal species that prospers mainly on dissipative sandy beaches along the temperate Atlantic coast of South America, from Brazil to Argentina (24–41 S). This large clam is considered a fast burrower, which lives buried in the sediment, migrating seasonally into the intertidal zone. The present study explores the effect of sediment grain size on the burrowing performance of this species, to elucidate the influence of granulometry on the alongshore distribution of the A. mactroides population. Laboratory trials were performed with clams of different sizes, to study the influence of grain size on the burial rate. Clam distribution was analyzed along a 32 km coastal fringe whose granulometric composition varies from very fine to coarse sand. The values of the mean burrowing rate index, a measurement of clam mobility, suggest that burrowing is fast to very fast in fine and medium sand and becomes slower toward areas with extreme particle size (very fine and coarse sand). The burial time of A. mactroides was positively correlated with shell length: small animals can burrow into substrates that may exclude larger animals. Adults clams burrowed in a very limited range of sand grain sizes. They displayed fastest burial times in grain sizes typical of dissipative beaches, i.e., fine to medium sand. Patchy distribution and density variation of A. mactroides alongshore reflect the relation between grain size and burrowing performance: the population is absent in sites with the highest proportion of coarse sands, its density increases in patches with the highest proportion of fine and medium sand and peaks at a site with the highest proportion of fine sand. Results indicate that the discontinuous distribution of A. mactroides along its range could be due to a postsettlement process. Clams can potentially recruit on a wide morphodynamic range, but only may thrive in beaches which sand grain size allows them a rapid reburial during migratory and local movements.